Akhlak dan Hubungannya Dengan Aqidah Dalam Islam - Nurhayati Nurhayati (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2014)
Islam is a religion that teaches the truths and values are universal and eternal. He has the ability to expand in line with the pace of technological development and civilization. Qur'an is still and will continue to have a function as a way of life for Muslims in any part of the earth, for the present and the days to come. In determining the position of the moral teachings of Islam, Islam has a theoretical foundation and purpose of its own. This is certainly not independent of the overall teachings of Islam which is based on the Qur'an and hadith. Morals have a very important position in Islam, because the scope of Islam, can not be separated from the three components, namely belief, Shari'ah and morals. Three things are mutually supportive and are closely related to one another. Creed is a person's belief in the Unseen, such as faith in God, as summed up in the six pillars of faith. Shari'ah, also known as worship, a way or ways that must be done every Muslim in an effort to get closer to his Creator, such as establishing and other prayers that are already mentioned in the pillars of Islam. While the character is the attitude of every human being conducted for the perfection of faith and shari'a or worship. Islam adalah suatu agama yang mengajarkan kebenaran-kebenaran dan tata nilai yang universal dan kekal. Dia mempunyai kemampuan untuk mengembang sejajar dengan laju perkembangan teknologi dan peradaban. Al-Qur’an masih dan akan tetap mempunyai fungsi sebagai pedoman hidup bagi umat Islam di bagian bumi manapun, untuk masa kini dan masa-masa akan datang. Dalam menetapkan ajaran mengenai kedudukan akhlak dalam Islam, maka Islam mempunyai landasan teoretik dan tujuannya tersendiri. Hal ini tentunya tidak terlepas dari ajaran Islam secara keseluruhan yang bersumber pada al-Qur’an dan hadith. Akhlak memiliki kedudukan yang sangat penting dalam Islam, dikarenakan ruang lingkup Islam, tidak bisa lepas dari tiga komponren, yaitu akidah, syari’at dan akhlak. Tiga hal ini saling mendukung dan memiliki keterkaitan erat antar satu dengan lainnya. Akidah merupakan keyakinan seseorang kepada yang gaib, seperti beriman kepada Allah SWT sebagaimana tersimpul dalam rukun iman yang enam. Syari’ah, disebut juga dengan ibadah, merupakan jalan atau cara-cara yang wajib dilakukan setiap muslim dalam upaya mendekatkan diri dengan Khaliq-Nya, seperti mendirikan shalat dan lainnya yang yang telah disebutkan dalam rukun Islam. Sedangkan akhlak merupakan sikap dari setiap manusia yang dilakukan demi kesempurnaan akidah dan syari’ah atau ibadahnya. Kata Kunci: Pendidikan, Akhlak, Islam